PENGATURAN PEMBAGIAN HAK KEWARISAN KEPADA AHLI WARIS DALAM HUKUM WARIS ISLAM BERDASARKAN KOMPILASI HUKUM ISLAM (KHI) - Indah Sari (UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA, 2017)
There are many Indonesian Muslims who do not know how to distribute their inheritance. Islamic doctrine told us to dispense immediately properties after someone died, and that is the moment when a person has the legal rights as a heir. Islamic Law Compilation Book II, that regulate procedure of inheritance for Muslims, prescribe who has the rights of inheritor and how to distribute the inheritance. It is also written there how to dissolve some dispute on inheritance things. This writing focused on the arrangement of inheritor rights as stated in Islamic Law Compilation based on Al-Qur’an and Hadith. It is finally expected that Indonesian Muslims understand of their rights and obligation on inheritance things as proposed in Islamic Law Compilation to bring about justice in our society. Keywords: Islamic Law, Islamic Inheritance Law, Islamic Law Compilation, Inheritance Rights, Inheritor